MARKETING AUDIT ON THE UKRAINIAN CONSULTING MARKET AND ITS ORGANIZATION MODELS - Yevtushenko, Natalia (Current Problems of Sustainable Development, 2026)
The article is devoted to the study of marketing audit issues as a separate type of consulting services in terms of identifying missed benefits from marketing activities of enterprises, and the selection and justification of effective models of its organization. An assessment of the consulting market in Ukraine for the period 2010-2024 was carried out in accordance with the proposed methodology, the results of which showed that it is during the crisis period that the interest of business entities in marketing and marketing consulting services increases. The demand for marketing audit services in the consulting market has been proven and the reasons for the increase in demand for this type of consulting services have been identified. The main reasons for the increased demand for marketing audit services are: irregular planning and lack of cost optimization processes; frequent changes in consumer behavior against the background of a decline in their solvency; increased competition and increased rivalry between market participants for consumers and resources; rapid digitalization and unreasonable introduction of new digital technologies; lack of a structured approach to business scaling. The main principles of marketing audit are presented: comprehensiveness, systematicity, independence, and periodicity. Three models of consulting based on behavioral roles (expert, process, project) are presented for practical application, which are advisable to use in the process of organizing a marketing audit, taking into account the nature of the enterprise’s problems, the specifics of its type of activity, and the professional qualities of consultants.